Do Algerian High School EFL Teachers Adapt Textbook Materials? - Nouichi , Fahima (Milev Journal of Research and Studies, 2022)
This paper attempts to assess Algerian high school EFL teachers’ practice of adapting English textbook materials. The latter doesn’t always meet the learners’ needs. Therefore, EFL teachers should adapt and develop these materials or design new ones to meet their learners’ needs and interests and to enhance and facilitate the process of learning. The present research explores if EFL teachers do adapt textbook materials according to the requirements of their specific classroom contexts through an interview and a questionnaire delivered to high school EFL teachers. The obtained results showed that Algerian high school EFL teachers believed that adapting textbook materials is required to facilitate the teaching/learning process and meet the learners’ needs. Moreover, most of the teachers confirmed that they are familiar with adaptation to meet their learners’ needs and achieve their teaching objectives since textbook materials do not always suit the learners’ levels and interests. They also agreed that adapting or designing new textbook materials is not an easy task, it requires time and energy.